Need satisfaction and sport motivation predict selection in a competitive youth soccer team over and above the relative age effect - Verner-Filion, J.; Gaudreau, P. (International Journal of Sport Psychology, 2023)
Throughout their development, youth athletes must endure several selection camps to make it into the most competitive organizations/teams. Researchers have shown that athletes born earlier in the calendar year are more likely to be selected into such teams. However, little is known about the psychological processes that distinguish the athletes who successfully get selected from those who don`t. This study investigated the role of motivational factors (i.e., need satisfaction and sport motivation) as predictors of selection into competitive youth soccer teams, over and above the relative age effect. Using a six-month prospective design, 67 youth elite soccer players (Mage = 12.29; SDage = 0.65) were followed throughout the selection camp. Results showed that autonomous sports motivation mediated the relationship between need satisfaction and team selection. These findings suggest that motivational processes are important factors to consider for talent identification and development of expertise in competitive youth sports.